Circulating B-vitamin biomarkers and B-vitamin supplement use in relation to quality of life in patients with colorectal cancer: results from the FOCUS consortium - Koole, Annalenn; Bours, Martijn J L; Geijsen, Anne J M R; Gigić, Biljana; Ulvik, Arve; Kok, Dieuwertje E; Brezina, Stefanie; Ose, Jennifer; Baierl, Andreas; Böhm, Jürgen; Brenner, Hermann; Breukink, Stéphanie O; et al. (The American journal of clinical nutrition, 2021)
B vitamins have been associated with the risk and progression of colorectal cancer (CRC), given their central roles in nucleotide synthesis and methylation, yet their association with quality of life in established CRC is unclear.To investigate whether quality of life 6 months postdiagnosis is associated with: 1) circulating concentrations of B vitamins and related biomarkers 6 months postdiagnosis; 2) changes in these concentrations between diagnosis and 6 months postdiagnosis; 3) B-vitamin supplement use 6 months postdiagnosis; and 4) changes in B-vitamin supplement use between diagnosis and 6 months postdiagnosis.We included 1676 newly diagnosed stage I-III CRC patients from 3 prospective European cohorts. Circulating concentrations of 9 biomarkers related to the B vitamins folate, riboflavin, vitamin B6, and cobalamin were measured at diagnosis and 6 months postdiagnosis. Information on dietary supplement use was collected at both time points. Health-related quality of life (global quality of life, functioning scales, and fatigue) was assessed by the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire 6 months postdiagnosis. Confounder-adjusted linear regression analyses were performed, adjusted for multiple testing.Higher pyridoxal 5′-phosphate (PLP) was cross-sectionally associated with better physical, role, and social functioning, as well as reduced fatigue, 6 months postdiagnosis. Associations were observed for a doubling in the hydroxykynurenine ratio [3-hydroxykynurenine: (kynurenic acid + xanthurenic acid + 3-hydroxyanthranilic acid + anthranilic acid); an inverse marker of vitamin B6] and both reduced global quality of life (β = −3.62; 95% CI: −5.88, −1.36) and worse physical functioning (β = −5.01; 95% CI: −7.09, −2.94). Dose-response relations were observed for PLP and quality of life. No associations were observed for changes in biomarker concentrations between diagnosis and 6 months. Participants who stopped using B-vitamin supplements after diagnosis reported higher fatigue than nonusers.Higher vitamin B6 status was associated with better quality of life, yet limited associations were observed for the use of B-vitamin supplements. Vitamin B6 needs further study to clarify its role in relation to quality of life.